Analisis Problem Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI pada Pelajaran Ekonomi - Tri Sufilla Wahyuniati; Retno Mustika Dewi; Retno Kushardini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to test the application of Problem-Based Learning in order to improve the learning outcomes of class XI students in economics lessons. This research is focused on international trade material that is applied to students in class XI MIPA 5 SMA Negeri 3 Mojokerto City for the 2022/2023 academic year, even the semester. This research method is a classroom action research which consists of four stages, namely planning, action, observation, and reflection and is carried out in two cycles with qualitative and quantitative analysis techniques. Qualitative data were obtained from observations or observations of learning processes and learning activities, while quantitative data were obtained from students' posttest results. The results showed that there was an increase in learning activities by researchers and the learning outcomes of class XI MIPA 5 students of SMA Negeri 3 Mojokerto City on international trade material from cycle I obtained 96.42% to 98.80 in cycle II. It can be concluded that learning by applying Problem-Based Learning is able to improve student learning outcomes obtained by a completeness percentage of 78.78% in cycle I with complete criteria and in cycle II obtained a completeness percentage of 90.90% with very complete criteria, this indicates there is an increase in student learning outcomes in each cycle.